2015
DOI: 10.1007/s00256-015-2299-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of rotator cuff tears using 3-Tesla MRI versus 3-Tesla MRA: a systematic review and meta-analysis

Abstract: Three-Tesla MRI appeared equivalent to 3-T MRA in the diagnosis of full- and partial-thickness tears, although there was a trend towards greater accuracy in the diagnosis of subscapularis tears with 3-T MRA. Three-Tesla 3D isotropic MRA appears equivalent to 3-T 2D MRA for all types of tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…In some cases however, it could fail to diagnose the presence of SSC tears [28], indirect signs, as LHBT subluxation must be analysed ( Figure 5). Diagnostic accuracy could be improved with MR arthrography in assessing rotator cuff tendon tears [29], essentially in the evaluation of SSC tears [30]. Lee recently reported that T1 SPIR is a more sensitive and accurate imaging sequence compared to T2 TSE in detecting SSC tendon tear on 3 T MRA [31].…”
Section: Radiographic Imagingmentioning
confidence: 99%
“…In some cases however, it could fail to diagnose the presence of SSC tears [28], indirect signs, as LHBT subluxation must be analysed ( Figure 5). Diagnostic accuracy could be improved with MR arthrography in assessing rotator cuff tendon tears [29], essentially in the evaluation of SSC tears [30]. Lee recently reported that T1 SPIR is a more sensitive and accurate imaging sequence compared to T2 TSE in detecting SSC tendon tear on 3 T MRA [31].…”
Section: Radiographic Imagingmentioning
confidence: 99%
“…44 However, the combination of patient characteristics, history, and clinical shoulder tests for the diagnosis of FT tears could improve the ability of MRI, 171 and a meta-analysis confirmed that 3.0-T MRI appeared equivalent to 3.0-T MRA. 96 In recent years, technological advances in arthroscopic shoulder surgery have made the surgical management of partial-thickness (PT) tears much less invasive and thereby more cost-effective. Consequently, the identification of a PT tear has become more meaningful.…”
mentioning
confidence: 99%
“…So far, the diagnostic accuracy of 7-T shoulder MRI is inferior to the results of 3 T studies published in the literature. In the detection of supraspinatus tears at 3 T, Mc Garvey et al [34] reported in their meta-analysis sensitivities of 85.7% and 80.5% and specificities of 99% and 100% for full-and partial-thickness tears, respectively. However, a high number of false positive results was reported in patients with adhesive capsulitis, where MRI predicted a rotator cuff pathology in 57.9 % while arthroscopy revealed an incidence of only 13.2% [35].…”
Section: Discussionmentioning
confidence: 99%